Corporate governance, shariah governance, and credit rating: A cross-country analysis from Asian Islamic banks - Muhammad Mansoor Baig; Nazima Ellahi; Arshad Hassan; Qaisar Ali Malik; Abdul Waheed; Naeem Ullah (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
This study aimed to investigate the association between corporate governance characteristics, shariah governance characteristics, and the credit rating of Asian Islamic banks. To do so, we collected data from 22 banks during the 2006-2018 period. In total, we observed 286 data points. Credit rating was measured through an adaption of the credit rating scale that measured the long term credit of Islamic banks on an ordinal scale. From these data, 19 scores (Aaa) were considered high credit ratings and 1 score (C) was considered a low credit rating. Descriptive statistics, correlations, and the ordered logit regression model were applied in a panel setting. We found that the board interlock, board independence, CEO duality, and board foreign directorship negatively affected credit ratings. We also found that the board size, board accounting, finance knowledge, presence of women on the board, shariah board size, presence of supervisory shariah board, the shariah board interlock, and presence of female shariah scholars all were positively associated with credit ratings. This study suggests that Islamic banks can access more funds with higher shariah compliance. As such, we concluded that evaluating organizations' credit ratings must consider shariah governance attributes as determinants of the credit rating of Islamic banks.
Keywords: 650; credit rating institutions; order logit model; shariah governance